BOOK REVIEWS (Journal of Finance, 1953)
Book reviewed in this article: Business Finance: Conference on Research in Business Finance . By U niversities ‐N ational B ureau C ommittee for E conomic R esearch . New York: National Bureau of Economic Research, 1952. Pp. xviii+340. $5.00. Money and Banking: A Study of Moneyflows in the United States . By M orris A. C opeland . New York: National Bureau of Economic Research, Inc., 1952. Pp. xxxii+338 +Appendixes 241. $7.50. The British Banking Mechanism . By W. M anning D acey . New York: Longmans, Green & Co., 1952. Pp. 203. $2.25 (trade); $1.80 (text). De Algemene Banken in Nederland (Inleiding tot de Economische Problematiek. Dell III: Bankwezen). By F. D e R oos . Utrecht: N.V. A. Oosthoek's Uitgevers Mij., 1949. Pp. xii+147. A Study of Savings and Savings Facilities in New York State, 1941 and 1950 . By W illiam E. D unkman . New York: New York State Bankers Association, 1952, Pp. x+147. $5.00 (paper). Readings in Business Cycles and National Income . By A lvin H. H ansen and R ichard V. C lemence . New York: W. W. Norton & Co., 1953. Pp. xi+588. $5.25. Money and Banking . By J ay L. O'H ara . New York: Pitman Publishing Corporation, 1948. Pp. xx+671. $5.00. Money and Economic Activity . Edited by L awrence S. R itter . Boston, Mass.: Houghton Mifflin Company, 1952. Pp. viii+404. $2.95 (paper). International Finance: United States Economic Policy and International Relations . By R aymond F. M ikesell . New York: McGraw‐Hall Book Co., 1952. Pp. xii+341. $5.00. Public Finance: The Federal Debt . By C harles C ortez A bbott . New York: Twentieth Century Fund, 1953. Pp. xvii+278. $4.00. The Federal Taxing Process . By R oy B lough . New York: Prentice‐Hall, 1952. Pp. x+506. $5.00. The Financial Problem of the City of New York . By R obert M. H aig , C arl S. S houp , and L yle C. F itch . New York: The Mayor's Committee on Management Survey, 1952. Pp. 551. Public Finance and Fiscal Policy . By R ichard W. L indholm . New York: Pitman Publishing Corp., 1950. Pp. xxvii+732. $5.50. The Taxation of Corporate Income in Canada . By J. R ichards P etrie . Toronto: University of Toronto Press, 1952. Pp. xvii+380. $7.00. U.S. Taxation of Foreign Entities . By N eil F. P hillips . Toronto, Canada: The Carswell Company, Limited, 1952. Pp. xxxviii+397. $8.50.